2009
DOI: 10.1111/j.1464-410x.2008.08128.x
|View full text |Cite
|
Sign up to set email alerts
|

One preoperative dose randomized against 3‐day antibiotic prophylaxis for transrectal ultrasonography‐guided prostate biopsy

Abstract: OBJECTIVE To compare the incidence of infective events between a single dose and 3‐day antibiotic prophylaxis for transrectal ultrasonography (TRUS)‐guided prostate biopsy. PATIENTS AND METHODS Patients were randomized to receive either one preoperative dose consisting of two ciprofloxacin 500 mg tablets 2 h before prostate biopsy, or 3 days of ciprofloxacin treatment. They had a clinical examination at study inclusion, the day of the biopsy and 3 weeks later. The day after the procedure all patients were cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…A recent multicenter study reported that 92.5% of the patients that underwent PB received FQ [5]. However, the duration of therapy is different in most studies [7,8]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent multicenter study reported that 92.5% of the patients that underwent PB received FQ [5]. However, the duration of therapy is different in most studies [7,8]. …”
Section: Discussionmentioning
confidence: 99%
“…5 Nosocomial exposure and duration of the exposure to fluoroquinolones appear to be related to the incidence of resistance. [5][6][7] With good tissue penetration and randomized trials supporting its benefit, ciprofloxacin is our choice of prophylactic agent for TRUS-guided prostate biopsy. 8,9 No difference between a prophylactic single dose administration and a 3-day course has been noted, but these studies are likely underpowered.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 No difference between a prophylactic single dose administration and a 3-day course has been noted, but these studies are likely underpowered. [7][8][9][10] A longer course is probably warranted in men with risk factors. 11 Alternative choices to attempt to cover the common organisms E. coli, K. pneumoniae, P. aeruginosa and Enterococcus include another fluoroquinolone, a second or third generation cephalosporin or gentamicin.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one of the main issues of concern has been the increasing resistance to antimicrobials of isolates from patients with sepsis following TRUSPB. Several publications have documented an alarming increase in resistance to fluoroquinolone among E. coli in post-TRUSPB infections [10,11], as well as to other antimicrobial agents such as ampicillin, ampicillin/sulbactam, trimethoprim/sulfamethoxazole and gentamicin [9,11]; extended spectrum β-lactamase (ESBL)-producing isolates have been increasingly recovered [12]. Over the years, there has been an increase of E. coli resistance to ciprofloxacin (up to 90%) accompanied by a concomitant increase in the rate of post-TRUSPB infectious complications [9,11].…”
Section: Introductionmentioning
confidence: 99%